Isolating the delay component of impulsive choice in adolescent rats - McClure, Jesse; Podos, Jeffrey; Richardson, Heather N. (Frontiers in Integrative Neuroscience, 2014)
Impulsive choice — the preference for small immediate rewards over larger delayed rewards — has been linked to various psychological conditions ranging from behavioral disorders to addiction. These links highlight the critical need to dissect the various components of this multifaceted behavioral trait. Delay discounting tasks allow researchers to study an important factor of this behavior: how the subjective value of a rewards changes over a delay period. However, existing methods of delay discounting include a confound of modifying reward sizes during the procedure. Here we present a new approach of using a single constant reward size to assess delay discounting. A complementary approach could hold delay constant and assess the utility of changing quantities of a reward. Isolating these behavioral components can advance our ability to explore the behavioral complexity of impulsive choice. We present the methods for isolating delay in detail, and further capitalize on this method by pairing it with a standard peak interval task to test whether individual variation in delay discounting can be explained by differences in perception of time in male and female adolescent rats. We find that rats that were more precise in discriminating time intervals were also less impulsive in their choice. Our data suggest that differences in timing and delay discounting are not causally related, but instead are more likely influenced by a common factor. Further, the mean-level change in our measure between postnatal day 28 and 42 suggests this test may be capturing a developmental change in this factor. In summary, this new method of isolating individual components of impulsive choice (delay or quantity) can be efficiently applied in either adolescent or adult animal models and may help elucidate the mechanisms underlying impulsivity and its links to psychological disorders.